Chromosome aberration in typical biological systems under exposure to low- and high-intensity magnetic fields. (2nd April 2020) - Calabrò, Emanuele; Goswami, Hit Kishore; Magazù, Salvatore
ABSTRACT: The aim of this study was to investigate the response of chromosomes in typical human and plant cells under applied low-frequency magnetic fields at low and high intensities. Neuronal-like cells and roots of Allium sativum and Vicia faba were used to investigate chromosome's response to a static and 50 Hz magnetic fields at intensities ranging from 1 mT to 0.8 T, generated by two Helmholtz coils driven by direct current or alternate current voltage. Vertex spectrometer and Olympus microscope with camera were used. A significant decrease in intensity of the phosphate bands in the DNA infrared region was observed by FTIR spectroscopy analysis after exposure of neuronal-like cells to static and 50 Hz magnetic field at low intensity of 1 mT, which can be explained assuming that uncoiling and unpackaging of chromatin constituents occurred after exposure. This effect was directly observed by microscope in roots of Allium sativum and Vicia faba under exposure to a static magnetic field at high intensity of 0.8 T. These findings can be explained assuming that exposure to both low- and high-intensity magnetic fields of chromosomes in typical human and plant cells induces uncoiling and unpackaging of chromatin constituents, followed by chromosome alignment towards the direction of applied magnetic field, providing further demonstration that magnetic fields can induce the orientation of organic macromolecules even at low-intensity values.